The evolution of agricultural productions in Buzău County during the period 1999 - 2010 - Raluca Necula; Diana Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Agriculture is an important sector of economic activity of the County, we observe in this respect,the special quality of the arable land. This is why it is necessary the knowledge not only of the agricultural productions, but also of the value of agricultural production, which we have analyzed in this paper .One of the main issues is that the level of crop productions is due to climate conditions for the period 1999-2010, but in great measure to the level of the existing technical-material endowment at the level of farms. For the animal production we observed that it has had a descending trend in this period, for the main categories of animals.
Keywords: 330; Agriculture; crop production; animal production; value of the agricultural production sector; agricultural services